Meningkatkan Kemampuan Berpikir Kritis Siswa Melalui Penerapan Model Pembelajaran Project Based Learning - Muh Musi’in (Universitas Muria Kudus, 2022)
This School Action Research is aimed at improving critical thinking skills in students of SMP Negeri 1 Tengaran through the application of the Project Based Learning (PJBL) learning model. The research subjects were students in classes VII, VIII, and IX with a total of 815 students, namely 256 students in class VII, 286 students in class VIII, and 273 students in class IX. The data collection technique used in this study is a qualitative descriptive analysis technique through observation which includes indicators of critical thinking, namely: (1) Formulating the problem; (2) Providing arguments; (3) Doing induction: (4) Doing deduction; (5) Performing evaluation, and (6) Drawing conclusions and taking action. The results showed that there was an increase in the achieved of score of 4 from the initial conditions of 3.91% to 28.14% in cycle I and 48.32% in cycle II. Therefore, it can be said that the Project Based Learning (PJBL) model that has been implemented has succeeded in increasing students' critical thinking skills.